A blend of formic acid, benzoic acid, and aliphatic alkanes mediates alarm recruitment responses in western carpenter ants, Camponotus modoc. Issue 4 (6th April 2020) - Renyard, Asim; Gries, Regine; Gries, Gerhard
Abstract: Formicine ants in distress spray alarm pheromone which typically recruits nestmates for help. Studying the western carpenter ant, Camponotus modoc Wheeler (Hymenoptera: Formicidae), our objectives were to (1) determine the exocrine glands that contain alarm recruitment pheromone, (2) identify the key alarm recruitment pheromone components, and (3) ascertain the pheromone components that are discharged by distressed ants. In Y‐tube olfactometer experiments, extracts of poison glands, but not of Dufour's glands, elicited anemotactic responses from worker ants. Gas chromatographic‐mass spectrometric analyses of poison gland extracts revealed the presence of (1) aliphatic alkanes (undecane, tridecane, pentadecane, heptadecane), (2) aliphatic alkenes [( Z )‐7‐pentadecene, ( Z )‐7‐ and ( Z )‐8‐heptadecene], (3) two acids (formic, benzoic), and (4) other oxygenated compounds (hexadecan‐1‐ol, hexadecyl formate, hexadecyl acetate). Testing the responses of worker ants in Y‐tube olfactometers to complete and partial synthetic blends of these compounds revealed that the acids and the alkanes are essential alarm pheromone components. In two‐choice arena bioassays, micro‐locations treated with synthetic alarm pheromone recruited worker ants. Acids and alkanes were abundant in the poison gland and the Dufour's gland, respectively, suggesting that the alarm pheromone components originate from both glands. Moreover, alarm pheromone sprays of ants differed in that all sprays contained formic acid but only some also contained alkanes, implying that ants can independently discharge the content of either one or both glands in accordance with the type of distress incident they experience. Abstract : Ants discharge alarm pheromone and defensive compounds to alert nest mates and subdue enemies. Studying the western carpenter ant, Camponotus modoc (Hymenoptera: Formicidae), we identified a blend of formic acid, benzoic acid, and aliphatic alkanes that attracts nest mates. Worker ants were attracted to point locations treated with synthetic alarm pheromone and attractive pheromone components were discharged by distressed ants.